The influence of capital structure towards company value: Industrial product sector / Mohd Khairunnizom Mahmud - Mahmud, Mohd Khairunnizom (2008)
Over a century capital structure had been used in financing both the major and minor player in the industrial sector in Malaysia. Capital structure is basically related to the debt-equity ratio. A company that issue bonds originally will increase their debt-equity ratio but instead if they issue stock their debt-equity ratio will be lesser. This is why the debt policy and equity ownership structure associated with each other. The study use time- series regression method to see the relationship between dependent and independent variables. The company value is the dependent variable of this study which total asset will be the proxy of the company value, while the independent variable is total debts to assets ratio, pre-tax income margin and total debt. According to the analysis for the year 1998 to 2007, which based on multiple linear regression found that, total debt and total debt to asset ratio are significantly influence the value of a firm while pre-tax profit margin do not significantly influence the value of a firm. This result had showed that only two of the outstanding independent variables can be used to measure the value of a firm.